Administrative and Legal Status of Law Enforcement Agencies as Subjects of Interaction with Financial Institutions in the Sphere of Combating the Legalization of Criminal Proceeds - A. V. Steblianko (Law and Safety)
The author has studied administrative and legal status of law enforcement agencies, which are the subjects of interaction with financial institutions in the field of combating the legalization of criminal proceeds. The contents of such categories as status, legal status, administrative and legal status have been clarified. Based on the analysis of the scientific literature, the author has determined that the rights and responsibilities are integral structural elements of the administrative and legal status. It has been noted that two main approaches to determining the structural elements of the administrative and legal status of law enforcement agencies were formed in administrative law science.